Non-karstic speleogenesis in sandstone rocks of Ukrainian Carpathians - Ridush, Bogdan (Problems of Geomorphology -and Paleogeography of the Ukrainian Carpathians and Adjacent Areas. Lviv University., 2023)
Due to the limited distribution of karst rocks and, accordingly, the small number of karst caves in the Ukrainian Carpathians, the caves of non-karst (pseudokarst, clastokarst) genesis attract considerable attention from cave researchers. The latter most often develop in massive and coarse-grained sandstone strata, usually found as part of flysch strata. The caves of non-karstic genesis are widely spread in the Cretaceous and Paleogene sandstone formations of the Ukrainian Carpathians. Most of them are developed in the massive sandstone of the Yamna Formation of the Palaeocene. The primary information about all caves on the territory of Ukraine is collected by the Commission for Accounting and Documentation of Caves of the Ukrainian Speleological Association (UkrSA), and by local caving clubs and individual researchers. Currently, the number of discovered caves in the sandstone of the Ukrainian Carpathians exceeds the number of mapped caves, not to mention their detailed description. The minimal information about each cavity includes the name, entrance coordinates, total length, and depth (amplitude) resulting from the cave survey. The additional description could contain knowledge about the history of the cave discovery, origin, geological settings, microclimate, sediments, inhabitants, paleontological and archaeological remains, etc. At present, many caves have been discovered in a few microregions: Kliuch Ridge, near Skole; the tract Drybka, between Yaremche and Yamna; on Sokilsky Ridge, and its south-eastern orographic continuation at tracts Protiate Kaminnia and Lekeche; Polonyna Runna; Lubnia Village; and Chorna Gora Ridge. Few yet not mapped cavities are known in Bubnyshche, Synytsia Mt., and some other sites. Most caves belong to three genetic types: tectonic, gravitational, and selective corrosion. The largest among tectonic caves is Tectonic (Dovbush) cave near Yamna Village, which is 388 m long. The longest selective-corrosion cave is 92 m long. Some caves with fissure-like morphology could also be of cryogenic origin. We suggest that the caves with the fissure-like morphology are the forms of paleoseismic dislocations.
Keywords: sandstone; pseudokarst; speleogenesis; selective corrosion; Ukrainian Carpathians